The superior memory effect of insightful learning: The role of associative novelty - Zhang, Zhonglu; Si, Yuye; Wang, Lan; He, Kaiyun (Acta Psychologica, 2025)
Previous research has confirmed the advantage of insightful learning in item memory, but its impact on associative memory, particularly the role of novelty, remains unclear. This study aims to investigate the role of novelty in insightful learning on associative memory and metamemory using a Chinese logogriph learning-testing paradigm. Participants were asked to judge whether the “Midi” word/character (the answer) matched the “Mimian” phrase (the problem) in both the high- and low-novelty conditions. Then they took immediate (2 min later) and delayed (24 h later) recognition tests to identify whether the “Mimian”-“Midi” (phrase-character) pairs were previously presented (old) or not (new), and assessed their retrospective confidences. Results showed that individuals had higher recognition rates for high- (vs. low-) novelty logogriphs, and higher retrospective confidence for recognized pairs. This research indicates that novelty enhances both associative memory and the confidence judgment of metamemory monitoring in insightful learning.
CRIS-Team Scopus Importer:2025-03-28
Keywords: Associative memory; Chinese logogriph; Insightful learning; Metamemory; Novelty